Increasing Educational Learning Outcomes Civic Education (PKn) Through Learning Models Cooperative Type Numbered Heads Together (NHT) at Class V MIS Ikhwanul Muslimin Tembung - Maida Puspa Ristika Ambarita; Azahra Sani, Adinda Salwa; Pastika Muhammad, Adeline; Eliazer Nadeak, Paiman; Sabeta Nainggolan, Rani; Ivana, Julia (Berpusi Publishing, 2023)
The low achievement of the Civics curriculum test for fifth grade students at SD No. 2 Great Ruins. This is because students are not interested in learning, do not feel compelled to ask questions or respond to their teacher's questions, and do not interact much with each other or their teacher. The purpose of this research is to improve students' academic achievement. this research is a group-based research known US Participatory Action Research (PAR), which combines elements of planning, observation, and reflection. Data collection techniques includes administering tests (before and after the facts), making in-depth observations, and keeping detailed records. On the other hand, both qualitative and quantitative approaches to data analysis are used. Information was collected qualitatively through classroom observations (such US observation notepad, teacher activities, and students' participation in class exercises) and quantitative information through tests of the material being studied. The results of this study showed that student learning outcomes increased, with an average value of 70.9% and an average percentage of 70% for student learning outcomes in Cycle I and an average value of 77.4% and an average percentage of 70% for student. learning outcomes in Cycle II respectively.